PENDAMPINGAN PEMANFAATAN GOOGLE FORM UNTUK MENDUKUNG ADMINISTRASI PKK KELURAHAN BEJI KECAMATAN UNGARAN TIMUR - Nur Ekaningsih; Swantyka Ilham Prahesti; Mega Mulianing Maharani (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2022)
Semarang Regency which has 19 sub-districts and 27 villages is an area with the industrial sector which is the largest contributor to the economy. So, the majority of the population is factory workers. The industrial center is in the Ungaran area which is the administrative center. Beji Village is one of the villages in the East Ungaran sub-district where the majority of the people work in industry. The majority of the workers are mothers. These women also participate in PKK activities, which are community activities that are held once a month. Because of their performance, the majority are factory workers, so that the administration in PKK activities still needs a lot of assistance. With administrative assistance, especially to make the work of these women more effective, the Google Form can be their solution as PKK movers to collect citizen data as PKK administrative data material.